2021
DOI: 10.3390/nu13113708
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity-Related Asthma: The Role of Nutrition and Nutrients in Prevention and Treatment

Abstract: Childhood obesity rates have dramatically risen in numerous countries worldwide. Obesity is likely a factor in increased asthma risk, which is already one of the most widespread chronic respiratory pathologies. The pathogenic mechanism of asthma risk has still not yet been fully elucidated. Moreover, the role of obesity-related inflammation and pulmonary overreaction to environmental triggers, which ultimately result in asthma-like symptoms, and the importance of dietary characteristics is well recognized. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 318 publications
(592 reference statements)
0
15
0
1
Order By: Relevance
“…Childhood obesity is at the root of multiple systemic comorbidities. These include, among others, unbalances in the endo-metabolic system (e.g., type 2 diabetes mellitus, dyslipidemia), respiratory system (e.g., obstructive sleep apnea, asthma), and gastrointestinal system including NAFLD and its evolutions as well as at the cardiovascular and musculoskeletal systems [ 16 , 17 , 18 , 19 , 20 ] ( Figure 1 ). The severity of these comorbidities increases proportionally to the degree of obesity [ 21 ].…”
Section: Childhood Obesity and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Childhood obesity is at the root of multiple systemic comorbidities. These include, among others, unbalances in the endo-metabolic system (e.g., type 2 diabetes mellitus, dyslipidemia), respiratory system (e.g., obstructive sleep apnea, asthma), and gastrointestinal system including NAFLD and its evolutions as well as at the cardiovascular and musculoskeletal systems [ 16 , 17 , 18 , 19 , 20 ] ( Figure 1 ). The severity of these comorbidities increases proportionally to the degree of obesity [ 21 ].…”
Section: Childhood Obesity and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…There is evidence that Mediterranean diet rich in fruit, vegetable and n-3 polyunsaturated fatty acids is protective for asthma development, exacerbations and asthma symptoms due to the positive impacts on inflammation, oxidation and microbial composition. Conversely, the Western diet—rich in saturated fatty acids and low in antioxidants—stimulates inflammation and may increase the risk of preschool wheezing and asthma with a negative effect on lung function [ 40 ]. In addition, childhood asthma may be influenced by maternal diet during pregnancy, particularly by the intake of certain foods such as fish or fruits and vegetables, and nutrients such as vitamin E, vitamin D, zinc or polyunsaturated fatty acids).…”
Section: Aetiopathogenesis Of the Bidirectional Relationship Between Obesity And Asthmamentioning
confidence: 99%
“…Epidemiologic evidences have shown that the overall prevalence and incidence of asthma are increased in obese individuals, and obesity is a risk factor for airway inflammation [ 32 , 38 , 39 , 40 , 41 , 42 ]. A recent meta-analysis, including six prospective cohort studies on the effect of body weight on future asthma risk, found a twice-higher risk in obese children compared with normal-weight ones, suggesting that obesity is an independent asthma risk factor for the youngest [ 43 , 44 ].…”
Section: Asthma In Young Female Adolescentsmentioning
confidence: 99%
“…Visceral obesity is responsible for a picture of mechanical obstruction in the lungs, resulting in airflow obstruction and altered lung volumes [ 43 ]. The relationship between obesity and asthma is complex [ 38 , 52 ]. In the Severe Asthma Research Program, an age/phenotype-dependent association was found: children with early onset asthma became obese, whereas there was no significant relationship between overweight/obesity and asthma duration in cases of late-onset asthma [ 32 , 53 ].…”
Section: Asthma In Young Female Adolescentsmentioning
confidence: 99%